THE APPLICATION OF LANGUAGE LEARNING STRATEGIES USED BY STUDENTS OF GENERAL ENGLISH CLASS OF INTERNATIONAL LANGUAGE PROGRAMS (ILP) KEDIRI AND THEIR CORRELATION WITH ACADEMIC ACHIEVEMENT - MARTINEZ, DIANA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Learning English as a foreign language is not as easy as learning the first and the second language since there are some differences among foreign language, first language, and second language that may cause problems in learning process. In learning foreign language, it needs some strategies to help learners. By applying the strategies, it will make the learning process becomes more effective. Since the goals of English course students are to enhance their English competence by practicing English, this study is aimed to examine the language learning strategies applied by students of General English class of ILP Kediri, and the correlation between the application of language learning strategies and academic achievement.This study used descriptive quantitative approach and survey related to correlation study. The subjects of this study were 46 students out of 201 students of General English class of International Language Programs Kediri taken by random sampling. The data were taken from Strategy Inventory for Language Learning (SILL) questionnaire completed by the students and their academic score at the end of the level.The results show that the use of overall language learning strategies falls into medium level, meaning that the students sometimes used those strategies. In particular, metacognitive strategies are found as the most frequently used strategies, followed by social, affective, compensation, cognitive, and memory strategies. There is a positive low significant correlation among metacognitive and social strategies and academic achievement. The possible reason of low correlation is caused by the context of English use since English is considered as a foreign language in Indonesia.In suggestion, it is expected that the teachers can introduce and emphasize the application of language learning strategies to the students, especially metacognitive and social strategies intended for the better academic achievement.Keywords: language learning strategies, English course students, Strategy Inventory for Language Learning (SILL) questionnaire